On Nation-to-Nation Partnership and the Never-Ending Business of Treaty-Making: Reflections on the Experience of the Crees of Eeyou Istchee (Eastern James Bay) - Scott, Colin H. (Anthropologica, 2020)
<div class="abstractSection abstractInFull" style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> This article discusses the successes of the Crees of Eeyou Istchee in the continual negotiation and renegotiation of their treaty relationship with the Quebec and Canadian governments but also queries how arrangements reached during more than four decades of treaty relationship, charting a course of proliferating entanglements with resource-extractive capitalism and state administration, both express and diverge from the “community of life” relational ontology of Cree activity on the land. While the Crees of Eeyou Istchee have achieved important successes in negotiating economic equity and territorial self-government and have not allowed themselves to be trapped in a once-and-for-all “settlement” of their rights, their negotiations with the state and with corporate entities reward certain Cree interests and positions over others. Compromises have occurred and development pathways chosen that increasingly challenge those who maintain as political priorities the defence of ecological diversity and integrity and accompanying Cree lifeways. Incommensurable premises of liberal capitalism and statehood have inhibited the conditions for the reproduction of Cree relationality, however nimbly the latter grapples with the former in reaching successive treaties and agreements <div style="box-sizing: border-box; color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Dans cet article, je me penche sur les succès obtenus par les Cris de Eeyou Istchee dans la (re)négociation perpétuelle de la relation de traité qu’ils entretiennent avec les gouvernements du Québec et du Canada. En même temps, j’explore comment la relation de traité, qui a dessiné pendant plus de quatre décennies des enchevêtrements proliférants avec le capitalisme d’extraction et l’administration étatique, reflètent tout en s’en distinguant l’ontologie relationnelle de type « communauté de vie » qui caractérise l’activité des Cris sur le territoire. Bien que les Cris de Eeyou Istchee aient engrangé d’importants succès dans la négociation de l’équité économique et de l’autonomie territoriale, et bien qu’ils ne se soient pas laissés piéger dans un « règlement » définitif de leurs droits, les négociations engagées avec l’État et les corporations ont favorisé certains intérêts et positionnements Cris par rapport à d’autres. Les compromis réalisés et les voies de développement empruntées mettent de plus en plus au défi ceux dont les priorités politiques restent la défense de la diversité et de l’intégrité écologiques et l’accompagnement des modes de vie cris. En ce sens, les présupposés incommensurables du capitalisme libéral et de l’État entravent la reproduction de la relationnalité crie, même si cette dernière lutte habilement contre les premiers dans la conclusion des traités et des ententes successives.